Evaluation of the impact of printed matter, video, and multimedia on the learning/teaching process in tropical diseases - Sarmento E Souza, M. F. [UNESP]; Cataneo, A. [UNESP]; Barraviera, B. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2001)
This study evaluated the impact of printed matter, video, and multimedia on the learning/teaching process in Tropical Diseases. Eighty-four of 90 fourth-year medical students at Botucatu School of Medicine of UNESP were evaluated. The students received a kit containing a textbook, a video, and a CD-ROM on the Clinical Study of Tetanus to prepare a seminar on the subject. They were then asked to complete a questionnaire, which led to the following conclusions: 67.86% read the textbook, 91.66% watched the video, and 77.38% explored the CD-ROM. These results were obtained observing the total number of students using each different media. When asked which of these media contributed most, the CD-ROM came out on top. The authors stress that this learning teaching process motivated the students by opening possibilities for new teaching alternatives in medicine.
Keywords: medical education; tropical diseases; multimedia; video; printed matter